种用鲕状赤铁矿制备的Fe/C复合多孔结构材料及其制备方法 (2018)
本发明公开了种用鲕状赤铁矿制备的Fe/C复合多孔结构材料及其制备方法，其特征在于：Fe/C复合多孔结构材料是由鲕状赤铁矿粉体和生物质粉体经混合、成型后，再在还原气氛下经热解和还原反应得到，其主要物相为生物质炭和零价铁。本发明的Fe/C复合多孔结构材料具有高开放孔隙率、高磁化率、高吸附性和高生物化学活性，适合在微污染水净化中应用，尤其是在富营养化水体同步脱氮处理中应用。 The invention discloses a Fe/C composite material prepared from oolitic hematite and adopting a porous structure as well as a preparation method of the Fe/C composite material. The Fe/C composite material is characterized in that oolitic hematite powder and biomass powder are mixed, molded and then subjected to pyrolysis and reduction reactions in a reducing atmosphere, the Fe/C composite material adopting the porous structure is obtained, and main phases of the Fe/C composite material are biomass charcoal and zero-valent iron. The Fe/C composite material has the high open porosity, high magnetic susceptibility, high absorption performance and high biochemical activity, is applicable to purification of slightly-polluted water and is particularly applicable to simultaneous denitrification treatment of eutrophic water bodies.